Nitrogen–rich 1, 2‐bis(tetrazol‐5‐yl)ethane and its Carboxylate Derivative for Potential Energetic Materials. Issue 11 (22nd July 2016) - Yang, Chun Hai; Lu, Yi Ming; Yan, Meng Qin; Li, Jin; Wu, Jiao; Li, Qiao Yun; Yang, Jie; Shen, Lei; Yang, Gao Wen; Zou, Jian Hua
Abstract: Tetrazole and its derivatives with rich nitrogen atoms are usually considered as potential candidates for energetic materials. The different substituents may have an impact on either the rigidity and flexibility or the energetic performance of such compounds. Here, 1, 2‐bis(tetrazol‐5‐yl)ethane (H2 btze) was prepared from succinonitrile and sodium azide from a [2+3] cycloaddition reaction, which was further reacted with chloroacetic acid to afford 1, 2‐bis(tetrazol‐5‐yl)ethane diacetic acid (H2 btzeda). In order to explore their potential as energetic materials, differential scanning calorimetry (DSC) and thermogravimetric‐differential thermogravimetric (TG‐DTG) analyses were applied to investigate the thermal decomposition behavior of such compounds. Thermodynamic parameters (ΔH, ΔS and ΔG) and explosion property parameters (critical temperature of thermal explosion, detonation heat, specific volume of explosion, detonation temperature, detonation velocity, detonation pressure, working capacity) were calculated according to literature and the law of thermodynamics base on DSC data. The results show H2 btze and H2 btzeda with both high enthalpy can be used as potential energetic materials. Furthermore, H2 btze has higher specific volume of explosion (943.94 L.kg −1 ) but lower detonation temperature (1994.44 K), compared with trinitrotoluene (TNT). Abstract : H2 btze and H2 btzeda were prepared. Thermodynamics analysis and explosion property estimate of H2 btze and H2 btzeda indicate they have the certain potential as energetic material, H2 btze in particular. Besides, The substituted group may not only have an impact on the flexibility of H2 btze, but also the energetic performance of these compounds. we can improve certain explosion properties of H2 btze by modification methods, such as synthesis method of H2 btzeda, for our own purposes.